251 fs pulse generation with a Nd3+-doped Ca3Gd2(BO3)4 disordered crystal. Issue 55 (17th June 2015) - Pan, Zhongben; Ma, Jie; Xu, Honghao; Tang, Dingyuan; Cai, Huaqiang; Yu, Haohai; Zhang, Huaijin; Wang, Jiyang
<x xml:space="preserve">Abstract</x> Autocorrelation trace and spectrum of the mode-locked pulses.